A Facility at the National Nuclear Research Centre, Pelindaba, for the Calibration of Gamma Survey Meters Used in Uranium-Prospecting Operations - P. D. Toens; D. vas As; Constance M. Vleggaar (The Southern African Institute of Mining and Metallurgy)
A facility at the National Nuclear Research Centre, Pelindaba, for the calibration of gamma survey meters used in uranium-prospecting operations by P. D. TOENS, D.Sc. (Fellow), D. van ASt, M.Sc. (Visitor), and CONSTANCE M. VLEGGAAR, B.Se. (Visitor) Ground radiometric surveys in uranium prospecting have in the past suffered from two serious shortcomings. Owing to varying instrument sensitivity and the often arbitrary height at which readings are taken, it has been impossible to compare results obtained in different surveys and, moreover, to relate such readings to actual U30s concentrations. A set of calibration sources designed to overcome these problems has recently been constructed on the site of the National Nuclear Research Centre, Pelindaba. A discussion of the standards applied and the instrument calibration procedure is presented.